Absolute beginner's guide to security, spam, spyware and viruses - Walker, Andy (Que, 2005)
Batten down the hatches! Hackers, spammers and thieves (oh my!) are after you! The mere act of turning on an Internet-connected computer can put you, your family, and your personal finances at risk by exposing you to viruses, scam artists, hackers, identity thieves, and spammers. How do you fight back? Absolute Beginner's Guide to Security, Spam, Spyware and Viruses is your first line of defense. Clear, easy-to-understand definitions of viruses, spyware, and hackers will help you understand what you're up against everytime you go online. Then, you'll learn about other threats, such as identity theft, phishing, and other potential dangers you'll face in your everyday computing. Find out how to search out and destroy spyware, malware and other viscious programs that could potentially harm your computer. Then find out how to lock out hackers, spammers, and theives for good. We'll tell you how to immediately cut the risk of being attacked in half - in less than 10 minutes! Protect your bank accounts, digital photos, digital music collection, masters thesis, and everything you hold near and dear on your computer with the help of the Absolute Beginner's Guide to Security, Spam, Spyware and Viruses .